2021
DOI: 10.1101/2021.06.15.448359
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A new adaptive procedure for estimating perceptual thresholds: the effects of observer bias and its correction

Abstract: Adaptive threshold estimation procedures sample close to a subject's perceptual threshold by dynamically adapting the stimulation based on the subject's performance. Yet, perceptual thresholds not only depend on the observers' sensory capabilities but also on any bias in terms of their expectations and response preferences, thus distorting the precision of the threshold estimates. Using the framework of signal detection theory (SDT), independent estimates of both, an observer's sensitivity and internal process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…left movement more noticeable than right). Including the bias can lead to improper fits in rare cases [34], and it has been found that participants could voluntarily shift their central bias, causing changes in threshold values, but the slope parameter remained relatively unchanged [32]. Since we had no a priori reason to expect a bias, we constrained the mean of the psychometric curve to zero for all participants.…”
Section: Discussionmentioning
confidence: 99%
“…left movement more noticeable than right). Including the bias can lead to improper fits in rare cases [34], and it has been found that participants could voluntarily shift their central bias, causing changes in threshold values, but the slope parameter remained relatively unchanged [32]. Since we had no a priori reason to expect a bias, we constrained the mean of the psychometric curve to zero for all participants.…”
Section: Discussionmentioning
confidence: 99%
“…A bias can occur if a participant either habitually chose a particular side when they were unsure of the direction or if the visual system itself had a skewed mapping (i.e., left movement more noticeable than right). Including the bias can lead to improper fits in rare cases (Fioravanti et al, 2021), and it has been found that participants could voluntarily shift their central bias, causing changes in threshold values, but the slope parameter remained relatively unchanged (Morgan et al, 2011). Since we had no a priori reason to expect a bias, we constrained the mean of the psychometric curve to zero for all participants.…”
Section: Test-retest Reliabilitymentioning
confidence: 99%